COMPREHENSIVE EVALUATION OF THE EFFECT OF COMPENSATION, WORK ENVIRONMENT CONDITIONS, AND WORKLOAD ON EMPLOYEE JOB SATISFACTION LEVEL: CASE STUDY AT MC'DONALDS SIDOARJO - Sari, Intan Nurvita; Firdaus, Vera (International Journal of Economic Integration and Regional Competitiveness, 2024)
General Background: Employee job satisfaction is a critical factor that impacts organizational performance and productivity. In fast-food industries like McDonald's, job satisfaction is influenced by multiple factors, including compensation, work environment, and workload. Specific Background: McDonald's Sidoarjo employees have exhibited varying levels of job satisfaction, making it important to assess how these factors contribute to their satisfaction. Knowledge Gap: Previous research has not fully explored the interaction between compensation, work environment, and workload on job satisfaction within fast-food chains in developing countries. Aims: This study aims to analyze the effects of compensation, work environment, and workload on employee job satisfaction at McDonald's Sidoarjo. Results: The findings reveal that compensation has a significant negative effect on job satisfaction, while both the work environment and workload exhibit significant positive effects. High compensation does not necessarily lead to higher job satisfaction, suggesting that other factors, such as work environment and workload, play a more prominent role. Novelty: This study highlights the unique negative relationship between compensation and job satisfaction in this context, contrary to common assumptions. Implications: The results suggest that improving the work environment and managing workload effectively are more important for enhancing employee satisfaction than focusing on compensation alone. Organizations should prioritize fostering healthy workplace conditions and balanced